2018
DOI: 10.3389/fnins.2018.00543
|View full text |Cite
|
Sign up to set email alerts
|

Stereotaxic Exposure of the Central Nucleus of the Amygdala to Corticosterone Increases Colonic Permeability and Reduces Nerve-Mediated Active Ion Transport in Rats

Abstract: Background: Irritable bowel syndrome (IBS) is characterized by visceral pain and abnormal bowel habits that are worsened during stress. Evidence also suggests altered intestinal barrier function in IBS. Previously, we demonstrated that stereotaxic application of the stress hormone corticosterone (CORT) onto the central nucleus of the amygdala (CeA) induces colonic hyperalgesia and anxiety-like behavior in a rat model, however the effect on intestinal permeability and mucosal function remain to be evaluated.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Systemic administration of corticosterone in mice ( 20 ) and rats ( 43 ) or local administration to the central nucleus of the amygdala in rats ( 44 ) results in increased mucosal permeability and disruption of gut barrier function. The current study confirms this effect of corticosterone on intestinal mucosal permeability in the ileum and colon.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic administration of corticosterone in mice ( 20 ) and rats ( 43 ) or local administration to the central nucleus of the amygdala in rats ( 44 ) results in increased mucosal permeability and disruption of gut barrier function. The current study confirms this effect of corticosterone on intestinal mucosal permeability in the ileum and colon.…”
Section: Discussionmentioning
confidence: 99%
“…Since the OAL model does not lead to premature HPA axis activity or abnormal HPA axis activity in adulthood, it is possible that the mechanism of unpredictable ELS‐induced increase in colonic permeability differs from the mechanism described by Zheng et al where CORT‐induced activation of GR on colonic epithelial cells caused a decrease in tight junction proteins in colonic epithelial cells and an increase in colonic permeability 43 . We previously showed that activation of the CeA, with stereotaxically placed CORT pellets, induced colonic hyperpermeability 44 . Like the OAL model, stereotaxic placement of CORT pellets on the CeA does not affect circulating CORT levels 45 .…”
Section: Discussionmentioning
confidence: 91%
“…43 We previously showed that activation of the CeA, with stereotaxically placed CORT pellets, induced colonic hyperpermeability. 44 Like the OAL model, stereotaxic placement of CORT pellets on the CeA does not affect circulating CORT levels. 45 Therefore, it is plausible that a hyperactive amygdala might contribute to abnormal colonic permeability.…”
Section: Discussionmentioning
confidence: 97%